Population density and distribution patterns of Austruca annulipes (Ring-legged fiddler crab) in the mangrove of Bogowonto Estuary, Kulon Progo, Yogyakarta, Indonesia - RIZKY NUR, FADILAH; INGGRID TRIFENA, YULIA; ZHALZABILLA SHAFA, ALFITRA; WINDA SAGITA, ARMADHAN; RATNA, WIDYANINGTYAS; DITA, RAHMAYANI; DINDA PUTRI, PERMATASARI; IGUSTITA, IGUSTITA; DIAN, KUSUMA; SATRIA AJI, PRAMBUDI; GAVRIEL ENOS, BERLIN; ADITYA, TRIYANTO; et al. (Smujo.id, 2023)
Fadilah RN, Yulia IT, Alfitra ZS, Armadhan WS, Widyaningtyas R, Rahmayani D, Permatasari DP, Igustita, Kusuma D, Prambudi SA, Berlin GE, Triyanto A, Sutarno, Indrawan M, Dadiono MS, Rahim KABA, Setyawan AD. 2023. Population density and distribution patterns of Austruca annulipes (Ring-legged fiddler crab) in the mangrove of Bogowonto Estuary, Kulon Progo, Yogyakarta, Indonesia. Intl J Bonorowo Wetlands 13: 1-8. The mangrove forest ecosystem is a forest with coastal plant characteristics that are influenced by tides and tolerate high salt levels. Mangrove forests in Indonesia contain about 89 species of flora, and around 18% of their fauna are keystone species. Keystone species are species that play an important role in maintaining the balance of the ecosystem. Austruca annulipes (H. Milne-Edwards, 1837), or Ring-legged fiddler crab is one of the fauna species in the mangrove ecosystem, which has an important role in maintaining the balance of the food chain and nitrogen cycle, so the study of this species is very important for the sustainability of the ecosystem in mangrove area. This study aimed to determine the population density and distribution patterns of A. annulipes in the Mangrove Bogowonto Estuary Area, Kulon Progo, Yogyakarta, Indonesia. The research method was purposive random sampling using a 10m x 10m square plot. Furthermore, the identification of morphology and documentation of the activities of A. annulipes was carried out, and data were examined using calculations of crab density. Based on the research finding, the population density of A. annulipes is 0.9975 individuals/m2 . Calculating the Morisita Index of A. annulipes obtained a value of 1.38 with the category of clumped distribution patterns. Various factors influence this distribution, including abiotic factors such as soil moisture, temperature, air, salinity, and pH. In addition, the presence of vegetation has also affected the density of A. annulipes because it is used as a shelter and foraging among its roots.